(untitled) (Culturas Científicas, 2025)
This paper presents the Modal-Hamiltonian Interpretation (MHI) of quantum mechanics and shows how it provides a conceptually consistent and physically plausible solution to the measurement problem. By assigning a central role to the system’s Hamiltonian and its symmetries in determining the observables that acquire definite values, the MHI avoids the difficulties faced by other interpretations when dealing with non-ideal measurements. Its update rule ensures that the measurement pointer always acquires a definite value and allows one to distinguish between reliable and unreliable frequency measurements. Furthermore, the MHI proposes a physical model that complements von Neumann’s formal approach, conceiving measurement as a symmetry-breaking process through which previously inaccessible generators of the Hamiltonian become empirically accessible.